2003
DOI: 10.3109/13506120309041731
|View full text |Cite
|
Sign up to set email alerts
|

A model for amyloid fibril formation in immunoglobulin light chains based on comparison of amyloidogenic and benign proteins and specific antibody binding

Abstract: In an attempt to understand the mechanism of amyloid fibril formation in light chain amyloidosis, the properties of amyloidogenic (SMA) and benign (LEN) immunoglobulin light chain variable domains (VL) were compared. The conformations of LEN and SMA were measured using secondary and tertiary structural probes over the pH range from 2 and 8. At all pH values, LEN was more stable than SMA. The CD spectra of LEN at pH 2 were comparable to those of SMA at pH 7.5, indicating that the low pH conformation of LEN clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 37 publications
4
23
0
Order By: Relevance
“…Previous studies of SMA aggregation in solution in the absence of mica surfaces have shown that both fibrils and amorphous aggregates are found, depending on the conditions (14,32,33). When small wafers of mica are added to solutions of SMA at low concentration, a number of different types of deposit are observed on the mica (16).…”
Section: Comparison Of Aggregates Grown On Mica and In Solution-mentioning
confidence: 99%
“…Previous studies of SMA aggregation in solution in the absence of mica surfaces have shown that both fibrils and amorphous aggregates are found, depending on the conditions (14,32,33). When small wafers of mica are added to solutions of SMA at low concentration, a number of different types of deposit are observed on the mica (16).…”
Section: Comparison Of Aggregates Grown On Mica and In Solution-mentioning
confidence: 99%
“…As evidenced, the epitope recognized by this antibody was present within the first 30 amino acids, and in studies of peptides encompassing this region (Figure 3a and b), it was further localized to the N-terminal 22 residues with an EC 50 of 0.24 ± 0.01 nM for Len , a value comparable to that of the intact V L (EC 50 , 0.18 ± 0.03 nM). Notably, there was no reactivity with Len (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). More precisely, the structure recognized by mAb 11-1F4 was contained within the N-terminal 18 residues (EC 50 Len (1-18), 0.30 ± 0.10 nM).…”
Section: Mab 11-1f Binds To a Conformational Epitope Located Within Fmentioning
confidence: 99%
“…Taken together, these data indicate that the epitope present on LC fibrils is associated with the formation of a fibril-prone structure, that is, an amyloidogenic intermediate. This conclusion is supported by the fact that mAb 11-1F4 is a potent inhibitor of de novo LC fibrillo-genesis at sub-equimolar concentrations (27,30). The fact that the epitope also could be detected on Other investigators have generated antibodies reactive with cryptic epitopes exposed on Aβ (12,(31)(32)(33)(34)(35), TTR (36), prion (37,38), and β2-microglobulin (39) fibrils and assembly intermediates but not on the native precursors.…”
mentioning
confidence: 91%
“…The fact that the majority of light chains are resistant to amyloid formation has allowed comparisons of amyloidogenic and nonamyloidogenic V L domains to attempt to identify the cause of this predisposition. [34][35][36][37][38][39] It has been suggested that the formation of amyloid fibrils does not begin from the native state of a protein, but more likely from a partially folded state or an intermediate state. [40][41][42] Mutations and changes in conditions that lead to destabilisation of the native state may therefore serve to increase the population of an intermediate state, thereby enabling more molecules to be diverted into an amyloid-forming pathway.…”
Section: Introductionmentioning
confidence: 99%